2013
DOI: 10.7243/2050-1218-2-10
|View full text |Cite
|
Sign up to set email alerts
|

Culture conditions for growth of clinical grade human tissue derived mesenchymal stem cells: comparative study between commercial serum-free media and human product supplemented media

Abstract: Background: Large scale high quality and low cost production of clinical grade mesenchymal stem cells (MSCs) is critical for facilitating clinical research and potential stem cell therapies. Use of Fetal Bovine/Calf serum (FBS/FCS) for the clinical application carries a risk for transmission of zoonosis, therefore alternative xeno-free cell culture techniques have been evaluated. The commercial products for the culture of MSCs in xeno-free and/or serum free media such as STEMPRO® MSC SFM and MesenGro® are avai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 50 publications
1
8
0
Order By: Relevance
“…The reduction in cell viability after cryopreservation (M1–M3), compared to fresh cells (P2), is possibly due to osmotic stress which occurs during the freezing and thawing process, which proved to be more pronounced in cells cryopreserved in the absence of FBS (M2). The loss of cell viability was also observed in other studies after cryopreservation of different cell (Dhot et al, ; Vrhovac et al, ; Ribeiro et al, ; Inamdar and Inamdar, ; Kim et al, ; Munévar et al, ). It is noteworthy that the loss of viability did not affect the adhesion and clonicity shown in CFU‐F assay of UCIM‐MSC cryopreserved with medium M1 and M3, since the CFU‐F efficiency did not differ ( P < 0.05) in these groups to fresh cells.…”
Section: Discussionsupporting
confidence: 75%
“…The reduction in cell viability after cryopreservation (M1–M3), compared to fresh cells (P2), is possibly due to osmotic stress which occurs during the freezing and thawing process, which proved to be more pronounced in cells cryopreserved in the absence of FBS (M2). The loss of cell viability was also observed in other studies after cryopreservation of different cell (Dhot et al, ; Vrhovac et al, ; Ribeiro et al, ; Inamdar and Inamdar, ; Kim et al, ; Munévar et al, ). It is noteworthy that the loss of viability did not affect the adhesion and clonicity shown in CFU‐F assay of UCIM‐MSC cryopreserved with medium M1 and M3, since the CFU‐F efficiency did not differ ( P < 0.05) in these groups to fresh cells.…”
Section: Discussionsupporting
confidence: 75%
“…Numerous clinical studies have confirmed the safety of allogenic and autologous MSCs for treatment of human diseases [12,13]. Currently, MSCs are being investigated in terms of their therapeutic potential for inflammatory, autoimmune and degenerative conditions in preclinical and clinical studies [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…As things stand, bone marrow aspirate represents the most often used source [22] of MSCs. In addition, MSCs are obtained from adipose tissue [26], placenta as well as umbilical tissue [15] and blood [27,28], and peripheral blood [29] (Figure 1). Other sources, such as periosteum, trabecular bone, synovia, skeletal muscle, deciduous teeth, fetal pancreas, lung, liver and amniotic fluid, have also been reported [15].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations